"Stop Doing That!": Effects of Teacher Reprimands on Student Disruptive Behavior and Engagement. (July 2021) - Caldarella, Paul; Larsen, Ross A. A.; Williams, Leslie; Wills, Howard P.; Wehby, Joseph H.
Many teachers resort to using reprimands in attempts to stop disruptive student behavior, particularly by students with emotional or behavioral problems, although this may not be effective. This study examined short-term longitudinal data on teacher reprimands of 149 teachers in 19 different elementary schools across three states, as well as disruptive behavior and classroom engagement of 311 students considered at risk for emotional and behavioral disorders. A cross-lag analysis showed that teacher reprimands did not decrease students' future disruptive behavior or increase their engagement or vice versa. While teacher reprimands may suppress misbehavior momentarily, they do not appear to be effective in decreasing students' disruptive behavior or increasing their engagement over time. Limitations and implications are discussed.